Effects of low urea concentrations on protein-water interactions. Issue 1 (2nd January 2017) - Ferreira, Luisa A.; Povarova, Olga I.; Stepanenko, Olga V.; Sulatskaya, Anna I.; Madeira, Pedro P.; Kuznetsova, Irina M.; Turoverov, Konstantin K.; Uversky, Vladimir N.; Zaslavsky, Boris Y.
Abstract : Solvent properties of aqueous media (dipolarity/polarizability, hydrogen bond donor acidity, and hydrogen bond acceptor basicity) were measured in the coexisting phases of Dextran–PEG aqueous two-phase systems (ATPSs) containing .5 and 2.0 M urea. The differences between the electrostatic and hydrophobic properties of the phases in the ATPSs were quantified by analysis of partitioning of the homologous series of sodium salts of dinitrophenylated amino acids with aliphatic alkyl side chains. Furthermore, partitioning of eleven different proteins in the ATPSs was studied. The analysis of protein partition behavior in a set of ATPSs with protective osmolytes (sorbitol, sucrose, trehalose, and TMAO) at the concentration of .5 M, in osmolyte-free ATPS, and in ATPSs with .5 or 2.0 M urea in terms of the solvent properties of the phases was performed. The results show unambiguously that even at the urea concentration of .5 M, this denaturant affects partitioning of all proteins (except concanavalin A) through direct urea–protein interactions and via its effect on the solvent properties of the media. The direct urea–protein interactions seem to prevail over the urea effects on the solvent properties of water at the concentration of .5 M urea and appear to be completely dominant at 2.0 M urea concentration.